The effect of extension and loading of the carpus on radial rotation. Issue 8 (15th October 2013) - Bitton, Erez; Joseph, Rotem; Portman, Lena; Segev, Gilad; Meiner, Yaron; Shipov, Anna; Milgram, Joshua
Abstract: Objective: To describe the direction and magnitude of the rotation of the radius relative to the ulna during extension of the carpus and to describe the effect of carpal extension on internal and external rotation of the radius relative to the ulna. Study Design: In vitro experiment. Animals: Cadaveric canine thoracic limbs (n = 11). Methods: Eleven thoracic limbs were collected from 6 healthy mixed breed dogs of medium build. Each specimen was radiographed to ensure that the carpal and elbow joints were free of pathology. The elbow joint was disarticulated and the distal thoracic limb was prepared for biomechanical testing. Each specimen was stripped of soft tissue, leaving the soft tissues around the proximal aspect of the radius and ulna intact. The interosseous ligament, pronator teres muscle, and all the soft tissues distal to the distal metaphysis of the radius were also left intact. In the 1st part of the study, the rotation of the radius relative to the ulna was measured while extending the carpal joint using a system of weights and pulleys attached to the manus. In the 2nd part of the study, the internal and external rotation of the radius relative to the ulna was performed by applying an internal and external rotational load to the radius using a system of weights and pulleys attached to the radius. The internal and external rotation of the radius was measured with the carpus unloaded and with the carpus extended by applying a load of 5 kg to the manus. Results: Extension of the carpus resulted in internal rotation of the radius relative to the ulna. With the carpus extended under a maximum load of 2 kg, the mean (± SD) internal rotation of the radius was 4.3 ± 2.1° for all specimens. With the carpus unloaded, the mean internal and external rotation of the radius was 11.5 ± 2.9° and 22.5 ± 7.7° for all specimens, respectively. With the carpus loaded (extended under 5 kg load), the mean internal and external rotation of the radius was 3.3 ± 1.2° and 7.3 ± 2.0° for all specimens, respectively. The difference between internal and external rotation with the carpus loaded and unloaded was significant. Conclusion: Extending the carpus results in internal rotation, and proximal translation of the radius relative to the ulna. Loading the carpus in extension decreases the internal and external rotation of the radius relative to the ulna. A better understanding of the interaction between the carpus and the elbow may improve our understanding of the pathogenesis of elbow dysplasia.